Overview: food safety in food security and food trade - Unnevehr, Laurian J. (International Food Policy Research Institute, 2003)
Food safety is receiving heightened attention worldwide as the important links between food and health are increasingly recognized. Improving food safety is an essential element of improving food security, which exists when populations have access to sufficient and healthy food. At the same time, as food trade expands throughout the world, food safety has become a shared concern among both developed and developing countries. Governments in many countries have established new institutions, standards, and methods for regulating food safety and have increased investments in hazard control. This set of policy briefs describes how developing countries are addressing food safety issues in order to improve both food security and food trade, and discusses the risks, benefits, and costs when such policies are implemented.